(untitled) (Bangladesh Agronomy Journal, 2023)
A field experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka during 2014 on transplant aman rice var. BR11 (Mukta) under different levels of chemical fertilizers and green manures to evaluate its grain yield, grain quality and soil fertility status with incorporation of green manures. The experiment was carried out in a split- plot design with three replications. The level of fertilizers (0, 100, 75, 50% of recommended dose, RFD) was placed in main -plot and levels of green manures management (0, 5 and 10 t ha-1 each Mimosa invisa (Lajjaboti) and Sesbania spp. (Dhaincha) in sub-plot. Recommended dose of fertilizers of 83N, 21P, 37K, 11S and 1.5 Zn kg ha-1, were applied in the form of urea, triple super phosphate (TSP), muriate of potash (MoP), gypsum and zinc sulfate, respectively. Sixty-day old Mimosa invisa and Sesbania spp. were in - vitro incorporated before aman transplantation. Combined application of 75% RFD along with Mimosa invisa @ 10 t ha-1 was proved to be the best management in producing higher grain yield (7.25 t ha-1) and that was at par with treatment 50% RFD plus Mimosa invisa @ 10 t ha-1. Quality of grain was increased markedly in respect of amylose, carbohydrate, and protein as well. Furthermore, the treatment improved soil nutrient status in respect of organic matter, nitrogen, sulfur and Zn over no incorporations of green manures. So, addition of green manure like Mimosa invisa could cut fertilizer cost by 25-50%. Bangladesh Agron. J. 2022, 25(2): 67-72